2018
DOI: 10.1155/2018/4802396
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Retinopathy among Hypertensive Nondiabetic Patients at a Large Public Outpatient Clinic in Southwestern Uganda

Abstract: Background Routine testing of microalbuminuria and retinopathy is not done among patients with high blood pressure in resource-limited settings. We determined the prevalence of microalbuminuria and retinopathy and their risk factors among hypertensive patients at a large hospital in western Uganda. Methods We consecutively recruited nondiabetic patients with hypertension at the outpatients' clinic over a period of 3 months. Spot urine samples were tested for urine albumin. Direct fundoscopy was done to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In Uganda, a study was conducted among the patients attended hypertension clinic of the medical outpatients' department of Mbarara Regional Referral Hospital (MRRH), by Peter Kangwagye et al They found that the prevalence of microalbuminuria was 57.5% in patients with various stages of hypertensive retinopathy. 16 Nelly N Kabedi and his team studied the association of hypertensive retinopathy with cardiovascular disease, renal disorders and cerebrovascular disease in Congolese patients. In their study hypertensive retinopathy was found in 83.6% of the patients.…”
Section: Grade Of Hypertensive Retinopathymentioning
confidence: 99%
“…In Uganda, a study was conducted among the patients attended hypertension clinic of the medical outpatients' department of Mbarara Regional Referral Hospital (MRRH), by Peter Kangwagye et al They found that the prevalence of microalbuminuria was 57.5% in patients with various stages of hypertensive retinopathy. 16 Nelly N Kabedi and his team studied the association of hypertensive retinopathy with cardiovascular disease, renal disorders and cerebrovascular disease in Congolese patients. In their study hypertensive retinopathy was found in 83.6% of the patients.…”
Section: Grade Of Hypertensive Retinopathymentioning
confidence: 99%
“…Showed that micro albuminuria occurs in AMI and predicts early mortality 15 .Moreover, MA is independently associated with Cvd morbidity, after adjusting the known risk factors of the prevalence of CAD in men and women. The close relationship between MA and Coronary disease is greatly explained by the shared pathogen tic mechanisms of endothelial days function, systemic inflammation and vascular injury 16 ; it is reasonable to assume that such a relationship should exist regardless of the simultaneous presence or absence of diabetes.…”
Section: Introductionmentioning
confidence: 99%